STRATEGI PROMOSI MOST FM MEDAN PADA PROGRAM LAJANG SHOW MELALUI MEDIA SOSIAL INSTAGRAM - Fika Amanda Pania; Muhammad Husni Ritonga; Rina Devianty (Bajang Institute, 2023)
In an inceasingly modern era with current technological developments, the presence of new meia has an impact on radio operations which are inceasingly being abandone by the public. Radio need promotional innovations to maintain the existence of broadcast programs using social media. This study aims to determine the promotion strategy of Most FM Medan on lajang show program via instagram. The research uses a qualitative descriptive approach through observation, interviews and documentation. The result of indicate that Most FM Medan uses theory promotional mix is advertising, promotion, direct marketing, personal selling an public relation on lajang show